2018
DOI: 10.1051/matecconf/201819710002
|View full text |Cite
|
Sign up to set email alerts
|

Site response analysis for estimating seismic site amplification in the case of Banda Aceh - Indonesia

Abstract: The city of Banda Aceh is potentially exposed to a significant seismic hazard of seismic site amplification. Estimation of seismic site amplification of the city is urgently required for any mitigation efforts as the city is founded on a thick, soft layer. This study aims to estimate seismic site amplification of Banda Aceh's soil. Analytical models have demonstrated that they can simulate reasonably well the seismic ground motions amplification. The most widely used model is the equivalent linear approach. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Firat et al (2015) [23] agreed with this scenario, as soil conditions and local sites can influence the soil amplification (this was experienced in the Adapazari region before the Kocaeli earthquake in 1999). Furthermore, Yunita et al ( 2018) [42] found soil amplification factors for Banda Acheh, which is underlain by soft soil up to 4.3. Thus, the soil amplification factor should be used to estimate the amount of vibration received by the ground surface when a seismic event occurs.…”
Section: Plotting Map Of Soil Amplification Factormentioning
confidence: 99%
“…Firat et al (2015) [23] agreed with this scenario, as soil conditions and local sites can influence the soil amplification (this was experienced in the Adapazari region before the Kocaeli earthquake in 1999). Furthermore, Yunita et al ( 2018) [42] found soil amplification factors for Banda Acheh, which is underlain by soft soil up to 4.3. Thus, the soil amplification factor should be used to estimate the amount of vibration received by the ground surface when a seismic event occurs.…”
Section: Plotting Map Of Soil Amplification Factormentioning
confidence: 99%
“…Building upon this event, the earthquake parameter becomes an essential component to be considered in this study. The high occurrence of earthquakes in Aceh can be attributed to various factors, including the presence of seismic sources such as subduction zones and the Sumatra fault passing through the region [74][75][76]. In addition to earthquakes and tsunamis, the presence of active volcanoes also underlies the reason why disaster-related parameters are prioritized over others.…”
Section: Case Studymentioning
confidence: 99%
“…In 2018 Saidi, Aulia, Setiawan, Abdullah, and Hasan [18] simulated typical retail buildings in the city Banda Aceh using a response spectra curve. Yunita, Setiawan, Saidi, and Abdullah [19] investigated the seismic site amplification of the city of Banda Aceh's soft soil. This investigation suggested a ground motion amplification of Banda Aceh's soils of up to 4.3.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%